2012
DOI: 10.1007/s10194-011-0413-6
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between migraine and tension-type headache and alcohol drinking, alcohol flushing, and hangover in Japanese

Abstract: The aim of the study was to investigate associations between headache types and alcohol drinking, alcohol flushing, and hangover. Alcohol consumption is inhibited by the presence of inactive aldehyde dehydrogenase-2 (ALDH2) whose carriers are susceptible to alcohol flushing and hangovers. We conducted a cross-sectional study of the 2,577 subjects (men/women: 1,018/1,559) who reported having ever experienced headaches unrelated to common colds and alcohol hangovers among 5,408 (2,778/2,630) Tokyo health checkup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The same was reported in the literature [21]. It was also reported that consumption of alcoholic beverages aggravates or triggers migraine, which is a good explanation for this observation [22-24].…”
Section: Discussionsupporting
confidence: 79%
“…The same was reported in the literature [21]. It was also reported that consumption of alcoholic beverages aggravates or triggers migraine, which is a good explanation for this observation [22-24].…”
Section: Discussionsupporting
confidence: 79%
“…Using ICHD-3 beta, our study demonstrated a high one-year prevalence of headache disorders in Russia (67.5%) in accordance with a recent Russian study and many international studies using ICHD-2 (2,21). One-year prevalence of headache in other studies varied from 4.7% to 80.8% (2245). The highest one-year prevalence of headache was found in Brazil, Finland and Denmark (1,5,38).…”
Section: Discussionmentioning
confidence: 80%
“…A Japanese study was aimed at the connection among headache type, alcohol flushing, and hangover headache . Alcohol flushing is caused by inactive alcohol dehydrogenase 2 (ALDH2), and persons with alcohol flushing tend to get alcohol hangover and headache.…”
Section: Review Of Studies With Discussion Of Important Questions Andmentioning
confidence: 99%